Bilateral Recurrent Ocular Toxoplasmosis with Hydrocephalus in a 10-Year-Old Girl: A Case Report (Sir Salimullah Medical College Journal, 2026)
This case report was done in Sir Salimullah Medical College & Mitford Hospital in Bangladesh in March 2025.Through Clinical & laboratory investigations, imaging were helpful for confirmatory diagnosis. After confirmation patient was treated with Antitoxoplasma therapy & ventriculo-peritoneal (VP) shunt surgery. Clinical recording, pretreatment & post treatment photographs was documented properly. A 10-year-old girl presented with bilateral dimness of vision, double vision with inward deviation of right eye with headache. On examination there was right side abduction deficit & retinal examination revealed papilledema, multifocal chorio-retinitis(BE).She had a documented history of congenital ocular toxoplasmosis infection and hydrocephalus with triventriculomegaly (2015) which was resolved with anti-parasite & steroid but this patient was lost in follow ups, following recurrence of congenital infection after 10 year again underwent through imaging , lumber puncture for CSF analysis & serum serology for toxoplasma & started treatment with long term anti-toxoplasma, immunosuppressants & underwent successful VP shunt surgery in a tertiary neurology center & condition dramatically improved, steroid tapered & discharged with anti-toxoplasma drug for a period of three weeks followed by secondary prophylaxis, the patients is now on regular follow up. This case is being reported for its rarer & recurrent occurrence which started in intrauterine life & again recur, highlights the importance of long -term continuation of antimicrobial treatment with follow ups & through neuro-ophthalmologic evaluation in patients with systemic symptoms & history of congenital toxoplasma infections.Sir Salimullah Med Coll J 2025; 33: 140-143